Seawater analysis from cruise KH-14-6 in the western South Pacific Ocean along the GEOTRACES transect GP19 - Linjie Zheng; Tomoharu Minami; Shotaro Takano; Yoshiki Sohrin (PANGAEA, 2023)
This data contains the basic hydrological parameters, including temperature, salinity, potential density anomaly, potential temperature, dissolved oxygen, silicate, nitrate, phosphate, and chlorophyll-a concentrations, dissolved (d) Cd, dNi, dZn, dCu, dFe and labile particulate (lp) Fe concentrations in the western South Pacific Ocean along the GEOTRACES transect GP19 (~170°W, 64°S - equator). Seawater samples were collected using a clean CTD (Conductivity, Temperature, and Depth) sampling system with Niskin-X bottles during the Japanese GEOTRACES cruise KH-14-6 onboard the research vessel Hakuho Maru from December 2, 2014 to February 26, 2015. Filtered samples for the determination of dissolved trace metals (dMs) were passed through an AcroPak cartridge filter with a 0.8/0.2 μm pore size (Pall Life Sciences) and were transferred to 250-mL low-density polyethylene (LDPE) bottles (Nalgene). Samples for the determination of total dissolvable trace metals (tdMs) were not filtered. The seawater samples were acidified to pH ~2 with ultrapure HCl (Tamapure AA-10, Tama Chemicals) immediately after collection and were stored at room temperature in the laboratory for several years until analysis. An offline automated solid-phase extraction system (SPE-100, Hiranuma Sangyo) equipped with a column of Nobias Chelate-PA1 resin (Hitachi High-Technologies) was used to preconcentrate the trace metals (Al, Mn, Fe, Co, Ni, Cu, Zn, Cd, and Pb) in seawater (Minami et al., 2015; doi:10.1016/j.aca.2014.11.016). Unfiltered samples were first passed through a 0.45-μm pore size Millex syringe filter (Merck Millipore) and then introduced into the SPE-100 system. The labile particulate metal (lpMs) concentrations were calculated as the difference between tdMs and dMs. Trace metal concentrations were determined using a high-resolution inductively coupled plasma mass spectrometer (HR-ICP-MS, Element 2, Thermo Fisher Scientific) using the calibration curve method. Temperature was measured using a CTD sensor. Salinity was determined using a bench salinometer that was standardized based on the IAPSO standard seawater, and the oxygen content was measured using the Winkler method. Nutrient concentrations were determined by spectrophotometry using an automated analyzer onboard the vessel. Chlorophyll a (Chl. a) was collected on a 25-mm Whatman GF/F glass fiber filter and measured by fluorometry. Samples were collected using a clean CTD (Conductivity, Temperature, and Depth) sampling system with Niskin-X bottles (Sohrin and Bruland, 2011). Filtered samples for dMs determination were passed through an AcroPak cartridge filter with a 0.8/0.2-μm pore size (Pall Life Sciences) by the pressure of compressed air and were transferred to 250-mL low-density polyethylene (LDPE) bottles (Nalgene). Samples for tdMs determination were not filtered and were transferred from Niskin-X bottles to 250-mL LDPE bottles using a silicon tube. Filtered and unfiltered samples were placed in a cleanroom (Class 100) and acidified with 20% HCl (Tamapure AA-10, Tama Chemicals, Japan) to a pH of 1.9–2.0 within 24 h of sample collection.